Guarding our digital society's well-being - Leonardi, Stefano; Mahlmann, Peter; Meyer auf der Heide, Friedhelm; Spirakis, Paul G.; Weikum, Gerhard (e-Strategies, www.britishpublishers.com)

Why Robots Need Maps - Dynia, Miroslaw; Łopuszański, Jakub; Schindelhauer, Christian (Proc. of the 14th Colloquium on Structural Information and Communication Complexity (SIROCCO))

Competitive Maintenance of Minimum Spanning Trees in Dynamic Graphs - Dynia, Miroslaw; Korzeniowski, Miroslaw; Kutyłowski, Jarosław (Proc. of the 33rd International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM'07))

Using Mobile Relays for Ensuring Connectivity in Sparse Networks - Kutylowski, Jaroslaw

Competitive Maintenance of Minimum Spanning Trees under Stochastic Adversaries - Kutylowski, Jaroslaw

Orientation in a Trail Network by Exploiting its Geometry for Swarm Robotics - Dorigo, Marco; Hamann, Heiko; Szymanski, Marc; Wörn, Heinz; Shi, Yuhui (IEEE Swarm Intelligence Symposium, Honolulu, USA, April 1-5)

An analytical and spatial model of foraging in a swarm of robots - Hamann, Heiko; Wörn, Heinz; Sahin, Erol; Spears, Winfield; Winfield, Winfield (Swarm Robotics - Second SAB 2006 International Workshop)

A Space- and Time-Continuous Model of Self-Organizing Robot Swarms for Design Support - Hamann, Heiko; Wörn, Heinz (First International Conference on Self-Adaptive and Self-Organizing Systems (SASO 2007))
Designing and implementing artificial self-organizing systems is a challenging task since they typically behave non- intuitive and only little theoretical foundations exist. Predicting a system of many components with a huge amount of interactions is beyond human skills. The currently common use of simulations for design support is not satisfying, as it is time-consuming and the results are most likely sub- optimal. In this work, we present the derivation of an analytical, time-, and space-continuous model for a swarm of autonomous robots based on the Fokker-Planck equation. While the motion model is in most parts physically motivated, the communication model is based on a heuristic approach. A showcase application to a recently proposed scenario of collective perception in a huge swarm of robots with very limited abilities is given and the simulation results are compared to the model. Despite the high level of abstraction, the prediction discrepancies are small and the parameters can be mapped one-to-one from the model to the control algorithm. Finally, we give an outlook on the capabilities of the proposed model, discuss its limitations, and suggest an improvement that could reduce the number of empirically determined parameters.

Embodied Computation - Hamann, Heiko; Wörn, Heinz; Nagy, Marius; Nagy, Naya (Parallel Processing Letters)

From Micro to Nano and Swarm Robotics - Hamann, Heiko; Szymanski, Marc; Wörn, Heinz; Estana, Ramon; Xie, Ming; Dubowsky, Steven (Advances in Climbing and walking robots. Proceedings of 10th International Conference (CLAWAR'07), Singapore, July 16-18)
Current research in Micro, Nano and Swarm Robots as results of the European projects Miniman, MiCRoN and I-SWARM will be presented. First, the design and the control of 5 to 10cm3 sized mobile micro robots with five degrees of freedom will be shown. They can handle miniaturized parts as for example an optical component or a biological cell with a size in the micrometre-area with an accuracy of 100nm under a microscope or a raster-electron microscope. Second, the design and the control of a 1cm3-sized mobile untethered micro robot will be demonstrated. Here, the robot consists of five parts: the Piezzo locomotion module, the micro control unit, the communication unit, the navigation system and the micro gripper. The mobile robot can be guided and positioned in an arena with an accuracy of 5 micrometre and can be programmed and controlled over the wireless communication unit. Third, the design and the control of 3 × 3 × 3 mm3 sized micro-/nanorobots with 2 degrees of freedom will be presented. The transmission of energy and the communication between the robots is realized via infrared. The robot controller is fully integrated and has limited functionalities. Via basic sensors communication functions and elementary rules and behaviours the micro robot can act in a swarm consisting of hundreds and thousands of robots. Future applications could be monitoring-, inspection-, exploring-tasks etc. of big areas or objects.

Revising Type-2 Computation and Degrees of Discontinuity - Ziegler, Martin (Electronic Notes in Theoretical Computer Science)

Real Hypercomputation and Continuity - Ziegler, Martin (Theory of Computing Systems)

(Short) Survey of Real Hypercomputation - Ziegler, Martin (Lecture Notes in Computer Science)

Real Computational Universality: The Word Problem for a Class of Groups with Infinite Presentation - Meer, Klaus; Ziegler, Martin (Mathematical Foundations of Computer Science 2007)

On Faster Integer Calculations using Non-Arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (arXiv:0709.0624)
The unit cost model is both convenient and largely realistic for describing integer decision algorithms over (+,*). Additional operations like division with remainder or bitwise conjunction, although equally supported by computing hardware, may lead to a considerable drop in complexity. We show a variety of concrete problems to benefit from such NON-arithmetic primitives by presenting and analyzing corresponding fast algorithms.

Real Computability and Hypercomputation - Ziegler, Martin

Interactive Refinement of a Material Flow Simulation Model by Comparing Multiple Simulation Runs in one 3D Environment - Fischer, Matthias; Laroque, Christoph; Huber, Daniel; Krokowski, Jens; Mueck, Bengt; Kortenjan, Michael; Aufenanger, Mark; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2007))
The validation of material flow models as well as the selection of promising strategies for the generation of a successful experiment plan is a time-consuming process. A new approach is presented, which supports the simulation expert in his working process by giving him the opportunity to modify the simulated simulation run and afterwards compare the effects of his modification with the original setting, online and in one user interface, implemented by switching the visualizations between the simulation runs or opening up to 5 parallel 3D windows. The method developed therefore clones existing simulation runs online and allows the navigation within these existing simulation runs. The method has been implemented and is validated by a test model, which describes in detail the new working process of a modeler. New research questions are derived from this work, which will define following working steps.

Ein ganzheitlicher Ansatz zur immersiven 3D-Materialflusssimulation innerhalb der Digitalen Fabrik - Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)

Estimating Clustering Indexes in Data Streams - Buriol, Luciana S.; Frahling, Gereon; Leonardi, Stefano; Sohler, Christian (Proceedings of the 15th European Symposium on Algorithms (ESA))
We present random sampling algorithms that with probability at least 1 − δ compute a (1 ±ε)-approximation of the clustering coefficient and of the number of bipartite clique subgraphs of a graph given as an incidence stream of edges. The space used by our algorithm to estimate the clustering coefficient is inversely related to the clustering coefficient of the network itself. The space used by our algorithm to compute the number K 3,3 of bipartite cliques is proportional to the ratio between the number of K 1,3 and K 3,3 in the graph. Since the space complexity depends only on the structure of the input graph and not on the number of nodes, our algorithms scale very well with increasing graph size. Therefore they provide a basic tool to analyze the structure of dense clusters in large graphs and have many applications in the discovery of web communities, the analysis of the structure of large social networks and the probing of frequent patterns in large graphs. We implemented both algorithms and evaluated their performance on networks from different application domains and of different size; The largest instance is a webgraph consisting of more than 135 million nodes and 1 billion edges. Both algorithms compute accurate results in reasonable time on the tested instances.

On Testable Properties in Bounded Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 17th ACM-SIAM Symposium on Discrete Algorithms (SODA'07))
We study graph properties which are testable for bounded degree graphs in time independent of the input size. Our goal is to distinguish between graphs having a predetermined graph property and graphs that are far from every graph having that property. It is believed that almost all, even very simple graph properties require a large complexity to be tested for arbitrary (bounded degree) graphs. Therefore in this paper we focus our attention on testing graph properties for special classes of graphs. We call a graph family non-expanding if every graph in this family is not a weak expander (its expansion is O(1/log2 n), where n is the graph size). A graph family is hereditary if it is closed under vertex removal. Similarly, a graph property is hereditary if it is closed under vertex removal. Next, we call a graph property Π to be testable for a graph family F if for every graph G ε F, in time independent of the size of G we can distinguish between the case when G satisfies property Π and when it is far from every graph satisfying property Π. In this paper we prove thatIn the bounded degree graph model, any hereditary property is testable if the input graph belongs to a hereditary and non-expanding family of graphs.As an application, our result implies that, for example, any hereditary property (e.g., k-colorability, H-freeness, etc.) is testable in the bounded degree graph model for planar graphs, graphs with bounded genus, interval graphs, etc. No such results have been known before and prior to our work, in the bounded degree graph model very few graph properties have been known to be testable for any graph classes.

StrSort Algorithms for Geometric Problems - Sohler, Christian; Lammersen, Christiane (Proceedings of the 23rd European Workshop on Computational Geometry (EWCG))
In the StrSort model [2], the input is given as a stream, e.g. a sequence of points, and an algorithm can perform (a) streaming and (b) sorting passes to process the stream. A streaming pass reads the input stream from left to right and writes an output stream, which is the input of the next pass. A sorting pass is a black box operation that sorts a stream according to some partial order. In this paper, we develop algorithms for two basic geometric problems in the StrSort model. At first, we propose a divide-and-conquer algorithm that computes the convex hull of a point set in 2D in O(log2 n) passes using O(1) memory. Then we give a StrSort algorithm to compute a (1+ε)-spanner for a point set in Rd for constant d and constant epsilon that uses O(logd-1 n) passes and O(log n) space. This result implies a (1+ε)-approximation of the Euclidean minimum spanning tree in Rd, for constant d and ε.

Testing Expansion in Bounded-Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 48th Annual IEEE Symposium on Foundations of Computer Science (FOCS))

Small Space Representations for Metric Min-Sum k-Clustering and their Applications - Sohler, Christian; Czumaj, Artur (Proceedings of the 24th International Symposium on Theoretical Aspects of Computer Science (STACS'07))

Sublinear-time approximation algorithms for clustering via random sampling - Sohler, Christian; Czumaj, Artur (Random Structures & Algorithms)
We present a novel analysis of a random sampling approach for four clustering problems in metric spaces: k-median, k-means, min-sum k-clustering, and balanced k-median. For all these problems, we consider the following simple sampling scheme: select a small sample set of input points uniformly at random and then run some approximation algorithm on this sample set to compute an approximation of the best possible clustering of this set. Our main technical contribution is a significantly strengthened analysis of the approximation guarantee by this scheme for the clustering problems.The main motivation behind our analyses was to design sublinear-time algorithms for clustering problems. Our second contribution is the development of new approximation algorithms for the aforementioned clustering problems. Using our random sampling approach, we obtain for these problems the first time approximation algorithms that have running time independent of the input size, and depending on k and the diameter of the metric space only. © 2006 Wiley Periodicals, Inc. Random Struct. Alg., 2007A preliminary extended abstract of this work appeared in Proceedings of the 31st Annual International Colloquium on Automata, Languages and Programming (ICALP), pp. 396407, 2004.

A PTAS for k-means clustering based on weak coresets - Sohler, Christian; Monemizahdeh, Morteza; Feldman, Dan (Proceedings of the 23rd annual symposium on computational geometry (SoCG'07))

Efficient kinetic data structures for MaxCut - Sohler, Christian; Czumaj, Artur; Frahling, Gereon (Proceedings of the 19th Canadian Conference on Computational Geometry (CCCG))

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Smart Teams: Simulating Large Robotic Swarms in Vast Environments - Arens, Stephan; Buss, Alexander; Deck, Helena; Dynia, Miroslaw; Fischer, Matthias; Hagedorn, Holger; Isaak, Peter; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Nesterow, Viktor; Ogiermann, Adrian; Stobbe, Boris; et al. (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)
We consider the problem of exploring an unknown environment using a swarm of autonomous robots with collective behavior emerging from their local rules. Each robot has only a very restricted view on the environment which makes cooperation difficult. We introduce a software system which is capable of simulating a large number of such robots (e.g. 1000) on highly complex terrains with millions of obstacles. Its main purpose is to easily integrate and evaluate any kind of algorithm for controlling the robot behavior. The simulation may be observed in real-time via a visualization that displays both the individual and the collective progress of the robots. We present the system design, its main features and underlying concepts.

Local strategies for maintaining a chain of relay stations between an explorer and a base station - Dynia, Miroslaw; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Schrieb, Jonas (Proceedings of the nineteenth annual ACM symposium on Parallel algorithms and architectures - SPAA '07)

Efficient Collision Detection for Point and Polygon Based Models - Klein, Jan

Position-based Routing Strategies - Rührup, Stefan

Single-Minded Unlimited Supply Pricing on Sparse Instances - Briest, Patrick; Krysta, Piotr (Proceedings of the 17th ACM-SIAM Symposium on Discrete Algorithms (SODA))

Energy-Efficient Broadcast Scheduling for Speed-Controlled Transmission Channels - Briest, Patrick; Gunia, Christian (Proceedings of the 17th International Symposium on Algorithms and Computation (ISAAC))

Die Analyse von Estimation-of-Distribution-Algorithmen auf ausgewählten Funktionen - Degener, Bastian

Distributed random digraph transformations for peer-to-peer networks - Mahlmann, Peter; Schindelhauer, Christian (Proceedings of the eighteenth annual ACM symposium on Parallelism in algorithms and architectures - SPAA '06)
We study the problem of designing an adaptive hash table for redundant data storage in a system of storage devices with arbitrary capacities. Ideally, such a hash table should make sure that (a) a storage device with x% of the available capacity should get x% of the data, (b) the copies of each data item are distributed among the storage devices so that no two copies are stored at the same device, and (c) only a near-minimum amount of data replacements is necessary to preserve (a) and (b) under any change in the system. Hash tables satisfying (a) and (c) are already known, and it is not difficult to construct hash tables satisfying (a) and (b). However, no hash table is known so far that can satisfy all three properties as long as this is in principle possible. We present a strategy called SPREAD that solves this problem for the first time. As long as (a) and (b) can in principle be satisfied, SPREAD preserves (a) for every storage device nearly optimal, with high probability, guarantees (b) for every data item, and only needs a constant factor more data replacements than minimum possible in order to preserve (a) and (b).

Online Multi-path Routing in a Maze - Rührup, Stefan; Schindelhauer, Christian (Proc. of the 17th International Symposium on Algorithms and Computation (ISAAC 2006))

SAN Optimal Multi Parameter Access Scheme - Schindelhauer, Christian; Schomaker, Gunnar (5th International Conference on Networking (ICN))
Storage Area Networks commonly consist a more or less static set of n data servers that handle a dynamic collection of m documents. Such SANs can minimize the access time to documents by distributing each document among several servers, allowing users to access documents in parallel. This paper describes an efficient solution for providing parallel access to multiple hard disks for popular content. In extension to previous approaches we provide an efficient and elegant hash table data structure for utilizing the full capacity of each data server. Concerning the dynamics, documents as well as server may be added or removed from the system causing only local changes. We consider sequential and parallel access to data in the average case. For the average time model we present a fast optimal algorithm.

Improved Bounds for Online Multi-Path Routing in Faulty Mesh Networks - Rührup, Stefan; Schindelhauer, Christian

Predictive Replication and Placement Strategies for Movie Documents in heterogeneous Content Delivery Networks - Schomaker, Gunnar; Loeser, Christoph; Schubert, Matthias (5th International Conference on Networking (ICN).)
In previous publications there have been several proposals regarding replica generation and placement of movie content in content-distribution-networks or P2P overlays. Within this paper we extend approaches for heterogeneous placement scenarios described in prior publications. Therefor we presume heterogeneous server peers' bandwidth, HD capacity, and movie popularities. Movie documents are replicated and placed onto server peers with respect to the predicted popularity values. Thus each document aims to gain fair networks resources according to its popularity. We present simulation results of heuristics of different placement strategies and compare them with a near optimal technique.

Realizing Multilevel Snapshots in Dynamically Changing Virtualized Storage Environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (5th International Conference on Networking (ICN))

Size equivalent cluster trees (SEC-Trees) realtime rendering of large industrial scenes - Kortenjan, Michael; Schomaker, Gunnar (4th International Conference on Virtual Reality, Computer Graphics, Visualization and Interaction (Afrigraph 2006))
#hniid 2484

Reliable Broadcasting Without Collision Detection - Kutyłowski, Jarosław; Zagórski, Filip (SOFSEM 2006: Theory and Practice of Computer Science)
We propose a dynamic, ad-hoc communication network consisting of mobile units that can warn about traffic jams on motorways. Our goal is to provide a practical, low cost solution. Therefore we consider very simple wireless communication hardware, without collision detection, with very small bandwidth and a probabilistic model of link failure. We provide a complete system architecture. For this purpose we design and analyze solutions for size approximation, leader election and broadcasting. Our algorithms are fine-tuned for fast operation in a practical setting. We provide both a theoretical and experimental evaluation of our solutions. Our contribution is much different from the previous work, where either pure theoretical models with a pure theoretical analysis are provided or algorithms working in practical models are evaluated only through simulations.

Influence of adaptive data layouts on performance in dynamically changing storage environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (14th Euromicro International Conference on Parallel, Distributed, and Network-Based Processing (PDP'06))
For most of today's IT environments, the tremendous need for storage capacity in combination with a required minimum I/O performance has become highly critical. In dynamically growing environments, a storage management solution's underlying data distribution scheme has great impact to the overall system I/O performance. The evaluation of a number of open system storage visualization solutions and volume managers has shown that all of them lack the ability to automatically adapt to changing access patterns and storage infrastructures; many of them require an error prone manual re-layout of the data blocks, or rely on a very time consuming re-striping of all available data. This paper evaluates the performance of conventional data distribution approaches compared to the adaptive virtualization solution V:DRIVE in dynamically changing storage environments. Changes of the storage infrastructure are normally not considered in benchmark results, but can have a significant impact on storage performance. Using synthetic benchmarks, V:DRIVE is compared in such changing environments with the non-adaptive Linux logical volume manager (LVM). The performance results of our tests clearly outline the necessity of adaptive data distribution schemes.

Self-Coordinating Systems: The Next Challenge in Research on Distributed Systems
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

New trends in parallel and distributed computing - Monien, Burkhard; Meyer auf der Heide, Friedhelm

Directional Communication in Mobile Ad Hoc Networks - Grünewald, Matthias; Meyer auf der Heide, Friedhelm; Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus (New Trends in Parallel & Distributed Computing, 6th Int. Heinz Nixdorf Symposium)

Computing Clustering Coefficients in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana (Proceedings of the European Conference on Complex Systems (ECCS'06))
We present random sampling algorithms that with probability at least 1 - δ compute a (1 ± ǫ)- approximation of the clustering coefficient, the transitiv ity coefficient, and of the number of bipartite cliques in a graph given as a stream of edges. Our methods can be extended to approximately count the number of occurences of fixed constant-size subgraphs. Our a lgorithms only require one pass over the input stream and their storage space depends only on structural parameters of the graphs, the approxi- mation guarantee, and the confidence probability. For examp le, the algorithms to compute the clustering and transitivity coefficient depend on that coefficient but n ot on the size of the graph. Since many large social networks have small clustering and transitivity coe fficient, our algorithms use space independent of the size of the input for these graphs. We implemented our algorithms and evaluated their performance on networks from different appli- cation domains. The sizes of the considered input graphs varied from about 8, 000 nodes and 40, 000 edges to about 135 million nodes and more than 1 billion edges. For both algorithms we run experiments with a sample set size varying from 100, 000 to 1, 000, 000 to evaluate running time and approximation guarantee. Our algorithms appear to be time efficient for the se sample sizes.

Counting Triangles in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana

A Distributed O(1)-Approximation Algorithm for the Uniform Facility Location Problem - Sohler, Christian; Gehweiler, Joachim; Lammersen, Christiane (Proceeedings of 18th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this paper, we present a randomized constant factor approximation algorithm for the metric minimum facility location problem with uniform costs and demands in a distributed setting, in which every point can open a facility. In particular, our distributed algorithm uses three communication rounds with message sizes bounded to O(log n) bits where n is the number of points. We also extend our algorithm to constant powers of metric spaces, where we also obtain a randomized constant factor approximation algorithm.

Power-Aware Collective Tree Exploration - Dynia, Miroslaw; Korzeniowski, Miroslaw; Schindelhauer, Christian (Architecture of Computing Systems - ARCS)